Respuesta :

Ok so this is how i would solve a problem like this 

Simplifying -14 + 6b + 7 + -2b = 1 + 5b
 Reorder the terms: -14 + 7 + 6b + -2b = 1 + 5b
 Combine like terms: -14 + 7 = -7 -7 + 6b + -2b = 1 + 5b
 Combine like terms: 6b + -2b = 4b -7 + 4b = 1 + 5b
 Solving -7 + 4b = 1 + 5b
 Solving for variable 'b'.
 Move all terms containing b to the left, all other terms to the right.
 
Add '-5b' to each side of the equation. -7 + 4b + -5b = 1 + 5b + -5b
 
Combine like terms: 4b + -5b = -1b -7 + -1b = 1 + 5b + -5b
 
Combine like terms: 5b + -5b = 0 -7 + -1b = 1 + 0 -7 + -1b = 1
 
Add '7' to each side of the equation. -7 + 7 + -1b = 1 + 7
 
Combine like terms: -7 + 7 = 0 0 + -1b = 1 + 7 -1b = 1 + 7
 
Combine like terms: 1 + 7 = 8 -1b = 8

Divide each side by '-1'. b = -8
 
Simplifying b = -8 

Hope i helped!
krupa
IF IT HELPED PLEASE MARK AS BRAINLIEST ANSWER
-7 +4b = 1+ 5b
-7-1 = 5b -4b
-8 = b